A study on the comparative growth performance of three genotypes of ducklings with or without supplementary feeding in coastal areas of Bangladesh - Rahman, MM; Khan, MJ; Chowdhury, SD (Bangladesh Journal of Livestock Research, 2020)
An experiment was conducted with Muscovy, Pekin and Desi white ducklings for a period of 98 days in three villages of Noakhali district in order to know the effect of feed supplementation on growth performance and cost of production under scavenging system of rearing. A factorial experiment (2×3) was designed for 2 feeding regimes (control and supplemented) and 3 genotypes of duck. The feed supplements consisting of a mixture of rice polish, broken rice and wheat bran @ 50, 30 and 20% respectively. At 98 days of age, final live weight, live weight gain, feed conversion efficiency and survivability were highest in Muscovy and lowest in Desi white irrespective of feeding regimes. The differences among the genotypes were statistically significant (P<0.01) for final live weight and live weight grain. Feed conversion ratio was better in Muscovy than in Pekin and Desi white. The profit margin (Tk. 68.31vs 16.96) and cost benefit ratio (2.38 vs 1.38) were highest for Muscovy and lowest for Desi white ducklings. Feed had a significant (P<0.01) effect on total cost and genotypes also showed significant effect (P<0.0) on total cost. The profit margin differed significantly among the genotypes of bird and feeding regimes. From the study, it may be concluded that Muscovy ducklings could be profitably reared through supplementary feeding of 60g concentrate mixture daily under scavenging system in the rural areas and should be marketed at the age of 6 weeks. Bangladesh J. of Livestock Res. 20(1-2): 22-41, Jan-Dec 2013